1991
DOI: 10.1111/j.1464-410x.1991.tb15125.x
|View full text |Cite
|
Sign up to set email alerts
|

Results of Long-term Rice Bran Treatment on Stone Recurrence in Hypercalciuric Patients

Abstract: A series of 182 calcium stone formers with idiopathic hypercalciuria underwent treatment with rice bran for 1 to 94 months. Urinary calcium excretion was considerably reduced, but there was some increase in urinary phosphate and oxalate. Urinary excretion of magnesium and uric acid, serum calcium, magnesium, phosphate, uric acid, parathyroid hormone (PTH) and ALP was unaffected. There were no obvious changes in serum iron, zinc and copper even when patients were treated for long periods. Rice bran was well tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 9 publications
0
16
0
1
Order By: Relevance
“…Experimental and clinical works on the impact of a high-fiber diet on urinary parameters are scarce and contradictory. On the one hand, phytate in fibers can form complexes with calcium in the gut and reduce hypercalciuria [23, 24]. Fruits and vegetables, which are rich in fibers, decrease calcium oxalate supersaturation and increase citrate excretion [25].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and clinical works on the impact of a high-fiber diet on urinary parameters are scarce and contradictory. On the one hand, phytate in fibers can form complexes with calcium in the gut and reduce hypercalciuria [23, 24]. Fruits and vegetables, which are rich in fibers, decrease calcium oxalate supersaturation and increase citrate excretion [25].…”
Section: Discussionmentioning
confidence: 99%
“…10, 12 However, prior studies have shown mixed results on urinary calcium excretion, 13-16 and thus the association between fiber intake and stone formation is unclear. 13, 14, 17 …”
Section: Introductionmentioning
confidence: 99%
“…This feed has no known negative effects on DMI and has an adequate feed value for ruminants. Phytic acid from rice bran has been used to reduce dietary Ca availability to prevent renal calculi in humans (109,110) . Among common cereal brans, rice bran contains the highest phytic acid levels and presents the greatest in vitro binding potential (20 g Ca/kg bran) (111) .…”
Section: Dietary Inclusion Of Calcium Antagonistsmentioning
confidence: 99%